1997
DOI: 10.1111/j.1749-6632.1997.tb52360.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered Serotonin Function in Suicide

Abstract: Significant progress has been made in understanding psychosocial, psychological, and environmental factors associated with suicide; however, it is only recently that attention has been paid to the understanding of the neurobiology of suicide. There are several studies that implicate the serotonin (5-HT) system in suicide. Initial evidence was obtained from observations of low 5-hydroxyindoleacetic acid (5-HIAA) in cerebrospinal fluid (CSF) of depressed patients with a previous history of suicide attempts. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…That tri-peptide doubled the serotonin content of platelets when injected into pups subcutaneously [ 24 ]. 5 HT 2a receptors are increased in brain tissue and platelets in depression [ 25 ] which would agree with decreased levels in the synaptic cleft due to stimulated uptake. Also the decreased 5HIAA (5-hydroxy indole-acetic acid) in suicidal patients fit an increased uptake [ 26 ].…”
Section: Discussionmentioning
confidence: 85%
“…That tri-peptide doubled the serotonin content of platelets when injected into pups subcutaneously [ 24 ]. 5 HT 2a receptors are increased in brain tissue and platelets in depression [ 25 ] which would agree with decreased levels in the synaptic cleft due to stimulated uptake. Also the decreased 5HIAA (5-hydroxy indole-acetic acid) in suicidal patients fit an increased uptake [ 26 ].…”
Section: Discussionmentioning
confidence: 85%
“…[18][19][20][21] Using drugs with significant antagonistic properties toward the 5-HT 2A receptor (mianserin and mirtazapine), in addition to selective serotonin reuptake inhibitor (SSRI)s enhanced therapeutic responses in patients with major depression. 22,23) In an animal study, a reduction in the number of 5-HT 2A receptors caused by the administration of an antisense oligonucleotide decreased the duration of immobility in the forced swim test in mice.…”
Section: Discussionmentioning
confidence: 99%
“…They proposed that decreased levels of 5-HT in the synaptic cleft might result in depression. A study by Pandey (1997) found that suicidal patients had lower levels of 5-HT compared to normal subjects. A study by Wägner et al.…”
Section: Western Medicine’s Views About Emotion and Depressionmentioning
confidence: 99%